Time-varying trade cost (terms) and the distance puzzle - Richard Frensch; Michael Rindler (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2023)
We present a novel two-stage gravity specification with period-varying bilateral trade cost terms. We test our specification to confirm the benchmark result on declining international distance elasticities over time, using two new data sets. Analyzing period-varying bilateral trade cost derived from our specification offers additional insights: first, globalization has erased more than a third of the effect of distance on trade cost, mostly until the mid-nineties. Second, identifying period-varying bilateral trade cost separately for domestic vs. international trade offers a natural illustration to globalization - international trade cost are less persistent than domestic trade cost. Finally, reflecting the importance of general equilibrium adjustment, total bilateral trade cost - relating partial bilateral trade cost to multilateral resistances - are more appropriate to reflect globalization than partial bilateral trade cost.
Keywords: C23; F15; F40; O18; 330; Gravity; geography; panel models